Won't You Be My Neighbor? An Integrated Model of Urban Policy Interdependence. Issue 1 (January 2019) - Sapotichne, Joshua; Reese, Laura A.; Ye, Minting
This article explores local fiscal policy interdependence by proposing and testing a particular spatial modeling method to examine how different expenditure domains interact with neighboring jurisdictions. The analysis examines the extent of spatial interdependence by policy domain and explores the most robust way of determining neighbors for spatial analysis. It concludes that space matters in ways that need to be taken into account in the development of models explaining local spending and that different functional domains of expenditures have different scales of spatial effects. The extent of spatial interdependence varies by spending domain based on the amount of local government discretion and control over the policy area.